Phenological shifts in plankton dynamics reshape pressures on anchovy recruitment in the southern coastal waters of the Korean peninsula - Sun-Hee Lee; Juan Carlos Molinero; Eduardo Ramírez-Romero; Joo Myun Park; Marco Scotti; Li-Chun Tseng; Jung-Hoon Kang (Marine Environmental Research, 2026)

Plasma-engineered chitosan couples red-light bioenergetics to diabetic wound regeneration through programmable microenvironments - Lekshmi Rethi; Hoa Duc Chau; Erlina Febriani; Yan-Ting Chen; Szu-Yu Tung; Pei-Ru Jheng; Yu-Wen Tseng; Rou Li; Min-Lang Tsai; Chun-Chi Chang; Van Khiet Pham; Hieu Trung Nguyen; et al. (Carbohydrate Polymers, 2026)

Effects of elevated temperatures on oxidative stress, antioxidant and biochemical responses in the azooxanthellate coral Tubastraea aurea - Murugan Vasanthakumaran; Julia R. Beaudoin; Li-Chun Tseng; Jishnu Panamoly Ayyappan; Yi-Ta Shao; Mathan Ramesh; Tamilselvan Hema; Triparna Chatterjee; Subramani Thirunavukkarasu; Jiang-Shiou Hwang (Frontiers in Marine Science, 2026)
Introduction Coral reefs are highly productive marine ecosystems that support biodiversity, nutrient cycling, and coastal protection. Thermal stress associated with ocean warming threatens coral physiology by disrupting metabolism, antioxidant defenses, and tissue integrity. Tubastraea aurea , a stony coral with fleshy polyps and a calcareous skeleton, was investigated to determine how increasing temperature affects biochemical composition, oxidative stress responses, and morphological condition under controlled laboratory conditions. Methods Coral colonies were exposed to three temperature regimes, 21 °C, 25 °C, and 29 °C, to evaluate thermal stress effects. Biochemical parameters, including protein and glucose concentrations, were analyzed together with antioxidant biomarkers such as superoxide dismutase, catalase, glutathione S-transferase, and lipid peroxidation. Morphological observations were also conducted to assess tissue coverage, skeletal appearance, and overall physiological condition. Results Protein and glucose levels showed moderate alterations across temperature treatments, although statistical significance was not detected. Reductions were limited at 25 °C but became pronounced at 29 °C, suggesting disruption of protein synthesis and carbohydrate metabolism. Corals maintained at 21 °C and 25 °C retained healthy tissue coverage, whereas specimens exposed to 29 °C displayed darkened skeletal walls and restricted living tissue, indicating severe physiological damage. Antioxidant enzyme activities changed significantly under thermal stress. Superoxide dismutase activity increased progressively with temperature, reflecting enhanced reactive oxygen species production. Catalase activity rose at 21 °C and 25 °C, indicating adaptive detoxification responses. Lipid peroxidation levels increased under all temperature conditions, demonstrating oxidative membrane damage. Glutathione S-transferase activity also increased with temperature, confirming activation of cellular detoxification pathways. Discussion The findings demonstrate that sustained warming negatively affects the stability, antioxidant balance, and morphology of T. aurea . Elevated temperature redirected metabolic energy toward stress defense mechanisms instead of growth, tissue maintenance, and skeletal development. Increased antioxidant enzyme activities and lipid peroxidation confirmed the occurrence of oxidative stress and cellular damage under high temperature exposure. The severe tissue degradation observed at 29 °C suggests reduced coral resilience and highlights the potential consequences of ocean warming for coral survival, function, and persistence.

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Substrate-driven microbial diversity and functional potential of plastisphere biofilms in a dynamic coastal ecosystem of northeastern Taiwan - Priyanka Muthu; Sakcham Bairoliya; Gowri Krishna Girija; Li-Chun Tseng; Bin Cao; Jiang-Shiou Hwang; Ying-Ning Ho (Environmental Pollution, 2026)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Pathological and biochemical effects of polyethylene microplastic exposure in hydrothermal vent crab, Xenograpsus testudinatus - Mark June S. Consigna; Li-Chun Tseng; Chi Chou; Ching-Wen Huang; Yi-Ta Shao; Jiang-Shiou Hwang (Marine Pollution Bulletin, 2025)

Low high-temperature tolerance of the hydrothermal vent crab Xenograpsus testudinatus: Thermal biochemistry, survival rate and histological analyses, and habitat investigations - Li-Chun Tseng; Hong-Miao Chen; Chi Chou; Wen-Hung Twan; Yan-Ying Zhou; Lan Wang; Jiang-Shiou Hwang (Science of The Total Environment, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Impact of shallow hydrothermal vent waters on monsoonal copepod distribution and abundance around active volcanic island off northeast Taiwan, West Pacific - Anitha Mary Davidson; Li-Chun Tseng; Yan-Guo Wang; Jiang-Shiou Hwang (Science of The Total Environment, 2024)

Microbiome flexibility enhances the resilience of the potentially invasive coral Tubastraea aurea to abrupt environmental changes: Insights from a shallow water hydrothermal vent transplantation study - Gowri Krishna Girija; Li-Chun Tseng; Priyanka Muthu; Yu-Ling Chen; Ying-Ning Ho; Jiang-Shiou Hwang (Science of The Total Environment, 2024)

Mortality of mesozooplankton in an acidified ocean: Investigating the impact of shallow hydrothermal vents across multiple monsoonal periods - Anitha Mary Davidson; Li-Chun Tseng; Yan-Guo Wang; Jiang-Shiou Hwang (Marine Pollution Bulletin, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

Microbiome variability in invasive coral (Tubastraea aurea) in response to diverse environmental stressors - Gowri Krishna Girija; Li-Chun Tseng; Yu-Ling Chen; Pei-Jie Meng; Jiang-Shiou Hwang; Ying-Ning Ho (Frontiers in Marine Science, 2023)
The Indo-Pacific native azooxanthellate Tubastraea (Scleractinia) has been identified as an invasive marine species with substantial environmental, economic, and social implications worldwide. Despite their exceptional invasive capacity, our understanding of the role of their symbiotic microbiota in host resilience, as well as their response to ambient environmental conditions, remains limited. In this study, we analyzed the symbiotic bacterial communities found in the tissue and mucus of Tubastraea aurea from different habitats along the northeastern coast of Taiwan. These habitats included two extreme sites (a hydrothermal vent [HV] and a copper mining [CM] site) and two normal environments (inlet of a nuclear power plant [NPP] and a habitat adjacent to a conservation zone [CZ]). We employed full-length 16S rRNA sequencing (~1.5 kilobases) to determine coral-associated microbiome responses to local environments. Results showed significant variations in bacterial communities between corals from extreme and normal habitats. Chemoheterotrophic Endozoicomonas bacteria dominated the tissue samples from the HV and CM sites, whereas phototrophic Synechococcus cyanobacteria dominated the NPP and CZ sites. Hydrographic parameters such as pH, salinity, biological oxygen demand, turbidity, and concentration of heavy metals (e.g., Cu and Fe) increased at the HV and CM sites compared with those at the NPP and CZ sites. This difference created more stressful conditions at the HV and CM sites. The microbial assemblages associated with T. aurea exhibited a prevalence of diverse symbiotic bacteria that could potentially contribute to the host’s ability to adapt and survive in challenging ecological conditions. Therefore, these advantageous microorganisms, along with the host’s physiological mechanisms of dispersion, range expansion, and invasiveness, may enhance the resilience and ability of T. aurea to thrive in extreme environments.

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

Cold Dome Affects Mesozooplankton Communities during the Southwest Monsoon Period in the Southeast East China Sea - Yan-Guo Wang; Li-Chun Tseng; Xiao-Yin Chen; Rou-Xin Sun; Peng Xiang; Bing-Peng Xing; Chun-Guang Wang; Jiang-Shiou Hwang (Journal of Marine Science and Engineering, 2023)
In order to better understand the cold dome influence on zooplankton community structure, zooplankton samples were collected during the southwest monsoon prevailing period from the southeast waters of the East China Sea. To reduce the bias caused by different sampling months, the samples were collected in June 2018 and in June 2019. An obvious cold dome activity was proven by images of remote sensing satellites during the June 2018 cruise. In contrast, the research area was much affected by open sea high temperature and water masses during the June 2019 cruise. Significant differences in water conditions were demonstrated by surface seawater temperature, salinity, and dissolved oxygen concentrations between the two cruises. Nevertheless, no significant differences were observed concerning mesozooplankton in general, copepods, large crustaceans, other crustaceans, and pelagic molluscs between the June 2018 and June 2019 cruises. However, the mean abundance of gelatinous plankton was significantly different with 1213.08 ± 850.46 (ind./m3) and 2955.93 ± 1904.42 (ind./m3) in June 2018 and June 2019, respectively. Noteworthy, a significantly lower mean abundance of meroplankton, with 60.78 ± 47.32 (ind./m3), was identified in June 2018 compared to 464.45 ± 292.80 (ind./m3) in June 2019. Pearson’s correlation analysis also showed a highly positive correlation of gelatinous plankton and meroplankton with sea surface temperature (p

Nocturnal Eyes in Slipper Lobsters (Decapoda Scyllaridae): Physiological and Ecological Implications of Habitat Depths for Visual Traits - Oki Hayasaka; Hao-Yi Chang; Li-Chun Li; Yung-Che Tseng; Yi Ta Shao (Frontiers in Marine Science, 2022)
The light characteristics of an ecosystem drive evolutionary adaptations in visual traits, enhancing the diversity and abundance of species living there. The visual systems of crustaceans are highly diverse and often correspond to the optical properties of their preferred environments. Although habitat depth is known to greatly influence visual specialization in marine crustaceans, it remains unclear whether depth drives visual adaptions in nocturnal species. Slipper lobsters (Scyllaridae) are nocturnal benthic marine crustaceans distributed throughout a wide range of depths. In order to understand the visual adaptive capabilities of slipper lobsters inhabiting different depths, we characterized the eye structures of a shallow-water species ( Parribacus japonicas ), an intermediate-depth species ( Scyllarides squammosus ) and a deep-water species ( Ibacus novemdentatus ). Moreover, we measured by electroretinogram (ERG) the spectral sensitivities and temporal resolutions for each species using the following light stimuli: UV (λ max 386 nm), blue (λ max 462 nm), green (λ max 518 nm), yellow (λ max 590 nm), and red (λ max 632 nm). Our histological experiments show that all three species possess a typical superposition compound eye with square facets, and their ERG measurements revealed a single sensitivity peak for each species. Notably, peak spectral sensitivity corresponded to habitat depth, with the estimated peak for I. novemdentatus (493.0 ± 9.8 nm) being similar to that of S. squammosus (517.4 ± 2.1 nm), but lower than that of P. japonicus (537.5 ± 9.9 nm). Additionally, the absolute sensitivities at respective peak wavelengths for I. novemdentatus and P. japonicus were higher than that of S. squammosus . No differences were observed among the three species for maximum critical flicker fusion frequency (CFF max ) across light stimuli. However, P. japonicus had lower CFF max values than the other two species. These data suggest that all three nocturnal slipper lobsters are likely monochromatic and well adapted to dim light environments. Significantly, the deep-water slipper lobster displayed higher spectral sensitivities at shorter wavelengths than the shallow water species, but temporal resolution was not compromised.

Future trends and guidance for the triple bottom line and sustainability: a data driven bibliometric analysis - Ming-Lang Tseng; Chia-Hao Chang; Chun-Wei Remen Lin; Kuo-Jui Wu; Qing Chen; Li Xia; Bing Xue (Environmental Science and Pollution Research, 2020)
This study conducts a comprehensive literature review of articles on the triple bottom line (TBL) published from January 1997 to September 2018 to provide significant insights and support to guide further discussion. There were three booms in TBL publications, occurring in 2003, 2011, and 2015, and many articles attempt to address the issue of sustainability by employing the TBL. This literature analysis includes 720, 132, and 58 articles from the Web of Science (WOS), Inspec, and Scopus databases, respectively, and reveals the gaps in existing research. To discover the barriers and points of overlap, these articles are categorized into six aspects of the TBL: economic, environmental, social, operations, technology, and engineering. Examining the top 3 journals in terms of published articles on each aspect reveals the research trends and gaps. The findings provide solid evidence confirming the argument that the TBL as currently defined is insufficient to cover the entire concept of sustainability. The social and engineering aspects still require more discussion to support the linkage of the TBL and to reinforce its theoretical basis. Additionally, to discover the gaps in the data sources, theories applied, methods adopted, and types of contributions, this article summarizes 82 highly cited articles covering each aspect. This article offers theoretical insights by identifying the top contributing countries, institutions, authors, keyword networks, and authorship networks to encourage scholars to push the current discussion further forward, and it provides practical insights to bridge the gap between theory and practice for enhancing the efficiency and effectiveness of improvements.

Baseline diversity and host relationships of symbiotic caridean shrimps on the coast of northern Taiwan, southern East China Sea, prior to the establishment of a conservation area - Parinya Limviriyakul; Li-Chun Tseng; Yu-Hung Tsai; Jiang-Shiou Hwang; Tung-Wei Shih (Marine Biodiversity, 2020)

Effects of cadmium exposure on antioxidant enzymes and histological changes in the mud shrimp Austinogebia edulis (Crustacea: Decapoda) - Shagnika Das; Li-Chun Tseng; Chi Chou; Lan Wang; Sami Souissi; Jiang-Shiou Hwang (Environmental Science and Pollution Research, 2019)

Long-term study on seasonal changes in floristic composition and structure of marine macroalgal communities along the coast of Northern Taiwan, southern East China Sea - Showe-Mei Lin; Li-Chun Tseng; Put O. Ang; John Bolton; Li-Chia Liu (Marine Biology, 2018)

Chitosan-fabricated Ag nanoparticles and larvivorous fishes: a novel route to control the coastal malaria vector Anopheles sundaicus? - Kadarkarai Murugan; Jaganathan Anitha; Udaiyan Suresh; Rajapandian Rajaganesh; Chellasamy Panneerselvam; Al Thabiani Aziz; Li-Chun Tseng; Kandasamy Kalimuthu; Mohamad Saleh Alsalhi; Sandhanasamy Devanesan; Marcello Nicoletti; Santosh Kumar Sarkar; et al. (Hydrobiologia, 2017)

Predatory efficiency of the copepod Megacyclops formosanus and toxic effect of the red alga Gracilaria firma-synthesized silver nanoparticles against the dengue vector Aedes aegypti - Kandasamy Kalimuthu; Chellasamy Panneerselvam; Chi Chou; Showe-Mei Lin; Li-Chun Tseng; Kun-Hsien Tsai; Kadarkarai Murugan; Jiang-Shiou Hwang (Hydrobiologia, 2017)

Climate‐driven winter variations of Calanus sinicus abundance in the East China Sea - Juan Carlos Molinero; Li‐Chun Tseng; Lucia Lopez‐Lopez; Ulrich Sommer; Sami Souissi; Jiang‐Shiou Hwang (Fisheries Oceanography, 2016)
Global environmental changes threaten the sustainable use of resources and raise uncertainties regarding marine populations' responses in a changing Ocean. The pelagic copepods of the genus Calanus play a central role in shelf ecosystems transferring phytoplankton carbon to harvested populations, from boreal to temperate regions. Here we examined a 15‐yr time series of Calanus sinicus abundance in regards to climate forcing in the East China Sea. We identified a compound effect of the Pacific Decadal Oscillation ( PDO ) and the East Asian Winter Monsoon ( EAWM ) on environmental conditions in the East China Sea. Such climate influences not only a southward transport of C . sinicus from its population centres into the Taiwan area, but favours advantageous thermal conditions for the species as well. On the interannual scale, our results show that the population size of C . sinicus echoes climate‐driven temperature changes. Hence, the possibility of using the PDO and EAWM variability for assessing and predicting interannual abundance changes of C . sinicus in the East China Sea is considered. The observed close relationship between climate and C . sinicus may promote bottom‐up controls in the pelagic food web, further influencing the southern edge of the species' geographic distribution. Owing to the prominent role this species plays in food web dynamics these results might help integrative fisheries management policies in the heavily exploited East China Sea.

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Bio-efficacy potential of seaweed Gracilaria firma with copepod, Megacyclops formosanus for the control larvae of dengue vector Aedes aegypti - Kandasamy Kalimuthu; Show-Mei Lin; Li-Chun Tseng; Kadarkarai Murugan; Jiang-Shiou Hwang (Hydrobiologia, 2014)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Effects of sedimentation on the gorgonian Subergorgia suberosa (Pallas, 1766) - Li-Chun Tseng; Hans-Uwe Dahms; Nan-Jung Hsu; Jiang-Shiou Hwang (Marine Biology, 2011)

Faunal shift between two copepod congeners (Temora discaudata and T. turbinata) in the vicinity of two nuclear power plants in southern East China Sea: spatiotemporal patterns of population trajectories over a decade - Li-Chun Tseng; Ram Kumar; Qing-Chao Chen; Jiang-Shiou Hwang (Hydrobiologia, 2011)

Summer distribution of Noctiluca scintillans and mesozooplankton in the Western and Southern East China Sea prior to the Three Gorges Dam operation - Li-Chun Tseng; Ram Kumar; Qing-Chao Chen; Jiang-Shiou Hwang (Hydrobiologia, 2011)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

A novel normonoterpenoid from the stems of Cinnamomum reticulatum Hay - Ming-Jen Cheng; Wen-Li Lo; Wan-Shan Tseng; Hung-Chun Yeh; Chung-Yi Chen (Natural Product Research, 2010)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Importin KPNA2, NBS1, DNA Repair and Tumorigenesis - Shu-Chun Teng; Kou-Juey Wu; Shun-Fu Tseng; Chui-Wei Wong; Li Kao (Journal of Molecular Histology, 2006)

Independent [Ca2+]i increases and cell proliferation induced by the carcinogen safrole in human oral cancer cells - Jong-Khing Huang; Chun-Jen Huang; Wei-Chuan Chen; Shiuh-Inn Liu; Shu-Shong Hsu; Hong-Tai Chang; Li-Ling Tseng; Chiang-Ting Chou; Chih-Hung Chang; Chung-Ren Jan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)